128 Evaluation of SexedULTRA sex-sorted semen in timed artificial insemination programs for mature beef cows. (7th December 2018) - Thomas, J; Locke, J; Bonacker, R; Knickmeyer, E; Wilson, D; Vishwanath, R; Arnett, A; Smith, M; Patterson, D
Abstract: An experiment was designed to compare SexedULTRA TM sex-sorted semen and conventional semen in either fixed-time (FTAI) or split-time artificial insemination (STAI) of suckled beef cows. Units of sex-sorted (4.0x10 6 cells/unit) and conventional (25.0x10 6 cells/unit) semen were produced using contemporaneous ejaculates from three bulls. Cows (n=1620) across four herds were treated with the 7-d CO-Synch+CIDR protocol [administration of gonadotropin-releasing hormone (GnRH) and insertion of a progesterone insert (CIDR) on Day -10, followed by administration of prostaglandin F2α (PG) and CIDR removal on Day -3]. Cows were preassigned based on age, body condition score, and days postpartum to receive either FTAI or STAI with either conventional or sex-sorted semen. On Day -3, estrus detection aids (Estrotect ® ) were applied. In FTAI treatments, AI was performed on Day 0 at 66h after PG administration and CIDR removal, and GnRH was administered concurrent with AI. In STAI treatments, AI was performed on Day 0 (66h) or Day 1 (90h) based on Estrotect ® activation, with 100 μg GnRH administered to cows failing to express estrus by 90h. Pregnancy rates were affected (P=0.04) by the interaction of bull x semen type. Greater pregnancy rates were obtained with conventional versus sex-sorted semen for Bull A (64% versus 36%; P =0.001) and Bull B (72% versus 57%; P<0.01), whereas pregnancy rates did not differ between conventional and sex-sorted semen for Bull C (58% versus 52%). Pregnancy rates did not differ between STAI and FTAI approaches. However, total estrous response was greater (P<0.001) using STAI (84%) compared to FTAI (72%), and estrous cows obtained greater pregnancy rates (P<0.0001). In summary, relative fertility of sex-sorted and conventional semen varied among bulls. Although pregnancy rates were similar in STAI and FTAI, the increased estrous response observed in STAI may be advantageous if restricting use of sex-sorted semen to estrous cows.